A forming process of Mg-Gd-Zn alloy
By combining components, homogenized annealing and isodia angular extrusion processes in Mg-Gd-Zn alloy, dense needle-shaped LPSO phase and twisting belt are formed, which solves the contradiction between strong plasticity of the alloy and achieves the synchronization of strength and plasticity. Improved and expanded its application scope.
Patent Information
- Application Number
- CN202310496870.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-05
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-05-05
AI Technical Summary
Mg-Gd-Zn alloy has strong plasticity contradictions in conventional plastic forming processes, and it is difficult to improve its strength and plasticity at the same time, limiting its application range.
By combining the composition of Mg-Gd-Zn alloy, homogenized annealing and isometric angle extrusion processes, the specific steps include casting and machining the alloy ingot, performing homogenized annealing and extrusion treatment, heating control before and after extrusion, and gradually carrying out the Equidiametric angle extrusion and quenching after the extrusion is completed to form dense needle-shaped LPSO phases and twisting bands to enhance the mechanical properties of the alloy.
The synchronous improvement of strength and plasticity of Mg-Gd-Zn alloy has been achieved, which significantly improves its comprehensive mechanical properties and expands its application range.
Smart Images

Figure CN116516269B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of magnesium alloy deformation processing, and in particular to a plastic forming process of a Mg-Gd-Zn alloy. Background Art
[0002] As the lightest practical metal structural material, magnesium alloy has the advantages of low density, damping and shock absorption, and easy recycling, and is increasingly favored by aerospace, transportation and other fields. Among them, Mg-Gd-Zn alloys containing long-period ordered structures (LPSO) have excellent room temperature and high temperature strength performance, and have broader application potential than conventional AZ and ZK magnesium alloys. However, compared with aluminum alloys and steel structural materials, there is still a big gap between the strength and plasticity of Mg-Gd-Zn alloys. In particular, conventional plastic forming processes usually have a contradiction between strength and plasticity in the process of improving their mechanical properties, that is, it is difficult to improve the strength and plasticity of the alloy at the same time, which seriously limits the application range of the alloy.
[0003] As a severe plastic deformation process, equal-channel angular pressing has the advantage of accumulating plastic strain without changing the initial shape of the ingot. In recent years, it has been widely used in processing magnesium alloys to refine grains, accumulate dislocations and thus improve strength. However, the conventional equal-channel angular pressing process often reduces the elongation while improving the strength of the alloy. Therefore, there is an urgent need for a forming process that can simultaneously enhance the plasticized Mg-Gd-Zn alloy to improve its comprehensive mechanical properties and expand its scope of application. The present invention makes full use of the characteristics of the Mg-Gd-Zn alloy, and through the close cooperation between the alloy composition, the homogenization annealing system and the equal-channel angular pressing process, a significant simultaneous improvement in the strength and plasticity of the alloy is achieved, which has important guiding significance for the plastic forming and performance optimization of magnesium alloys containing LPSO phases. Summary of the invention
[0004] In order to simultaneously improve the strength and plasticity of the Mg-Gd-Zn alloy so that its comprehensive mechanical properties can meet higher service requirements, the present invention provides a forming process for the Mg-Gd-Zn alloy, and the specific technical solution is as follows.
[0005] A forming process of a Mg-Gd-Zn alloy mainly comprises the following steps:
[0006] A. Casting and machining a Mg-Gd-Zn alloy rectangular ingot with a cross-sectional side length of 40-60 mm and a length of 60-120 mm; the mass percentage composition of the alloy is Gd: 4.0-7.0%, Zn: 0.5-1.5%, and the rest is Mg and impurity elements that cannot be removed;
[0007] B. Perform homogenization annealing treatment on the ingot;
[0008] C. Perform equal-diameter angular extrusion on the homogenized annealed ingot in a die with an angle of 90°; before extrusion, heat the ingot and the die to 300-400°C and keep them warm for 1-3h; after the insulation, take out the ingot and put it into the die, and immediately use a hydraulic press to extrude the ingot along the length direction, for a total of 4-8 passes; the die and the sample are not heated in the middle, and the surface temperature of the ingot is controlled to be 20-50°C lower than that of the previous pass during each extrusion through natural cooling;
[0009] D.Quenching treatment is done immediately after extrusion, the water temperature is 20-40℃.
[0010] Preferably, in step B, the homogenization annealing process is: keep the temperature at 495-525°C for 15-40 hours, keep the temperature at 450-480°C for 3-10 hours, and then cool to room temperature at a rate of 1-10°C / min.
[0011] Preferably, in step C, the extrusion rate is 4-8 mm / min.
[0012] Preferably, in step C, the surface temperature of the ingot is 140-200°C at the end of extrusion.
[0013] Wherein, in each equal-diameter angular extrusion pass in step C, the ingot is swapped in length direction end to end, and the sample is not rotated along the length direction.
[0014] Wherein, after quenching in step D, the room temperature yield strength of the component along the extrusion direction is ≥200MPa, the tensile strength is ≥250MPa, and the elongation after fracture is ≥10%.
[0015] In the above scheme, the purpose of homogenizing the rectangular ingot mainly includes the following aspects: keeping at 495-525℃ for 15-40h is to promote the dissolution of the eutectic structure in the cast alloy, so that Gd and Zn atoms can fully diffuse into the Mg matrix, and provide sufficient solid solution atoms for the subsequent precipitation of a large number of LPSO phases in the α-Mg grains; in addition, it can make the ingot microstructure more uniform, eliminate casting residual stress, and improve its machinability. Keeping at 450-480℃ for 3-10h can promote the uniform formation of stacking faults inside the α-Mg grains, so that Gd and Zn elements can fully gather near the stacking faults, providing a favorable place for the subsequent large-scale nucleation and growth of needle-shaped LPSO phases. Then, it is cooled to room temperature at a rate of 1-10℃ / min. On the one hand, the solid solubility of Gd and Zn elements decreases with the decrease in temperature, so that they can precipitate at the stacking fault position in the form of LPSO phase; on the other hand, it prevents the temperature from dropping too fast and significantly reducing the diffusion rate of solid solution atoms, resulting in the precipitation of LPSO phase being severely inhibited. Through the homogenization treatment of this process, dense needle-shaped LPSO phase is regulated inside the α-Mg grains of the Mg-Gd-Zn alloy, laying the organizational foundation for the subsequent extensive LPSO phase torsion deformation.
[0016] Equal-diameter angular extrusion with an initial temperature of 300-400℃ and a cooling range of 20-50℃ per pass can not only prevent the alloy from cracking due to too low temperature during deformation, but also inhibit the non-basal slip of the alloy. After 1-3 extrusions with the alloy reversed in sequence and not rotated along the length direction, the dense needle-shaped LPSO phase tends to be arranged in parallel along a specific direction, and this orientation also leads to the inhibition of the basal slip of the LPSO phase. The subsequent 4-8 extrusions cause these needle-shaped LPSO phases to undergo extensive kink deformation and form a large number of kink bands under the condition that the basal and non-basal slips are simultaneously suppressed. These kink bands can hinder both dislocation movement and the expansion of microcracks, and can significantly improve the strength and elongation of the alloy at the same time. However, continuing to increase the number of extrusion passes will cause the LPSO phase to be broken and refined, and the kink bands will also decrease or disappear. The strength of the alloy can be slightly improved, but the elongation will be significantly reduced. Quenching treatment can maintain the structure after extrusion and prevent recrystallization from occurring during air cooling, thereby destroying the kink bands. Through the above-mentioned forming process, a large number of LPSO phase kink bands are obtained, achieving a significant simultaneous improvement in the strength and plasticity of the Mg-Gd-Zn alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a macroscopic photograph of the medium-diameter angular extrusion product of Example 1;
[0018] Figure 2 is the scanning electron microscope microstructure of the homogenized annealed alloy in Example 1;
[0019] Figure 3 This is the scanning electron microscope microstructure of the medium-diameter angular extrusion product of Example 1;
[0020] Figure 4 This is the scanning electron microscope microstructure of the medium-diameter angular extrusion product of Example 2;
[0021] Figure 5 This is the scanning electron microscope microstructure of the medium-diameter angular extrusion product of Example 1;
[0022] Figure 6 This is the scanning electron microscope microstructure of the medium-diameter angular extrusion product of Example 2;
[0023] Figure 7 This is the scanning electron microscope microstructure of the medium-diameter angular extrusion product of Example 3;
[0024] Figure 8 2 is the room temperature tensile stress-strain curve of the samples in the embodiments and comparative examples. DETAILED DESCRIPTION
[0025] The present invention has conducted a large number of comparative experiments by adjusting the forming process parameters. The present invention is further described by citing some embodiments below. These embodiments are used to illustrate the present invention, not to limit the present invention. Any improvement to the process of the present invention under the premise of the concept of the present invention belongs to the scope of protection of the present invention.
[0026] Example 1
[0027] A rectangular ingot with a size of 60×60×120mm was cast and machined, and the mass percentage of the ingot was Mg-7.0Gd-0.5Zn. The homogenization annealing process was to keep it at 525℃ for 15h, then keep it at 480℃ for 3h, and then cool it to room temperature at a rate of 10℃ / min. The homogenized ingot was subjected to equal-diameter angular extrusion in a mold with an angle of 90°. Before extrusion, the ingot and the mold were heated to 400℃ and kept for 1h. After the insulation was completed, the ingot was taken out and loaded into the mold, and the ingot was immediately extruded along the length direction with a hydraulic press. A total of 4 extrusions were performed. The head and tail of the ingot in the length direction were swapped in each pass, and the sample was not rotated along the length direction. The extrusion rate was 8mm / min. The mold and the sample are not heated during the process. The surface temperature of the billet is controlled to be 50°C lower than that of the previous one in each extrusion through natural cooling. The surface temperature of the billet is 200°C at the end of extrusion. It is immediately quenched in 25°C water to obtain the finished product. Figure 1 The scanned photo of the homogenized annealed alloy is shown in the attached Figure 2 The room temperature tensile mechanical properties along the length direction are listed in Table 1, and the stress-strain curves are shown in Appendix Figure 8 . See attached for scanned photos of the extruded product Figure 3 The room temperature tensile mechanical properties along the length direction are listed in Table 1, and the strain-strain curves are shown in Appendix Figure 8 .
[0028] Example 2
[0029] A rectangular ingot with a size of 40×40×60mm was cast and machined, and the mass percentage of the ingot was Mg-4.0Gd-1.5Zn. The homogenization annealing process was to keep the temperature at 495℃ for 40h, then keep the temperature at 450℃ for 10h, and then cool it to room temperature at a rate of 1℃ / min. The homogenized ingot was subjected to equal-diameter angular extrusion in a mold with an angle of 90°. Before extrusion, the ingot and the mold were heated to 300℃ and kept for 3h. After the insulation, the ingot was taken out and loaded into the mold, and the ingot was immediately extruded along the length direction by a hydraulic press. A total of 8 extrusions were performed. The head and tail of the ingot in the length direction of each pass were reversed in turn, and the sample was not rotated along the length direction. The extrusion rate was 4mm / min. The mold and the sample were not heated in the middle. The surface temperature of the ingot was controlled to be 20℃ lower than the previous pass by natural cooling during each extrusion. The surface temperature of the ingot was 140℃ at the end of extrusion, and it was immediately quenched in water at 30℃. See attached for scanned photos of the extruded product Figure 4 The room temperature tensile mechanical properties along the length direction are listed in Table 1, and the stress-strain curves are shown in Appendix Figure 8 .
[0030] Example 3
[0031] A rectangular ingot with a size of 50×50×100mm was cast and machined, and the mass percentage of the ingot was Mg-5.7Gd-1.1Zn. The homogenization annealing process was to keep the temperature at 515℃ for 25h, then keep the temperature at 465℃ for 7h, and then cool it to room temperature at a rate of 5℃ / min. The homogenized ingot was subjected to equal-diameter angular extrusion in a mold with an angle of 90°. Before extrusion, the ingot and the mold were heated to 350℃ and kept for 2h. After the insulation, the ingot was taken out and loaded into the mold, and the ingot was immediately extruded along the length direction by a hydraulic press. A total of 6 passes were extruded, and the ingot length direction was reversed in each pass, and the sample was not rotated along the length direction. The extrusion rate was 6mm / min. The mold and the sample were not heated in the middle, and the surface temperature of the ingot was controlled by natural cooling to be 30℃ lower than the previous pass during each extrusion. The surface temperature of the ingot was 170℃ at the end of extrusion, and it was immediately quenched in 30℃ water. The room temperature tensile mechanical properties along the length direction are listed in Table 1, and the stress-strain curves are shown in Appendix Figure 8 .
[0032] Comparative Example 1
[0033] A rectangular ingot with a size of 60×60×120mm was cast and machined, and the mass percentage content of the ingot was Mg-7.0Gd-0.5Zn. The homogenization annealing process was to keep it at 525℃ for 15h and then air cool it to room temperature. The homogenized ingot was subjected to equal-diameter angular extrusion in a mold with an angle of 90°. Before extrusion, the ingot and the mold were heated to 400℃ and kept warm for 1h. After the insulation was completed, the ingot was taken out and loaded into the mold. The ingot was immediately extruded along the length direction using a hydraulic press. A total of 4 passes were extruded. The ingots were swapped in length direction in each pass, and the sample was not rotated along the length direction. The extrusion rate was 8mm / min. The mold and the sample were not heated in the middle. The surface temperature of the ingot was controlled to be 50℃ lower than the previous pass during each extrusion by natural cooling. The surface temperature of the ingot was 200℃ at the end of extrusion, and it was immediately quenched in water at 25℃. Scanned photos of the extruded product are attached. Figure 5 The room temperature tensile mechanical properties along the length direction are listed in Table 1, and the stress-strain curves are shown in Appendix Figure 8 .
[0034] Comparative Example 2
[0035] A rectangular ingot with a size of 60×60×120mm was cast and machined, and the mass percentage of the ingot was Mg-7.0Gd-0.5Zn. The homogenization annealing process was 525℃ for 15h, then 480℃ for 3h, and then cooled to room temperature at a rate of 10℃ / min. The homogenized ingot was subjected to equal-diameter angular extrusion in a die with an angle of 90°. Before extrusion, the ingot and the die were heated to 450℃ for 1h. After the insulation, the ingot was taken out and loaded into the die, and the ingot was immediately extruded along the length direction by a hydraulic press. A total of 4 passes were extruded, and the ingot length direction was reversed in each pass, and the sample was not rotated along the length direction. The extrusion rate was 8mm / min. The mold and the sample were not heated in the middle, and the surface temperature of the ingot was controlled by natural cooling to be 50℃ lower than the previous pass during each extrusion. The surface temperature of the ingot was 250℃ at the end of extrusion, and it was immediately quenched in water at 25℃. See attached for scanned photos of the extruded product Figure 6 The room temperature tensile mechanical properties along the length direction are listed in Table 1, and the stress-strain curves are shown in Appendix Figure 8 .
[0036] Comparative Example 3
[0037] A rectangular ingot with a size of 40×40×60mm was cast and machined, and the mass percentage of the ingot was Mg-4.0Gd-1.5Zn. The homogenization annealing process was to keep the temperature at 495℃ for 40h, then keep the temperature at 450℃ for 10h, and then cool it to room temperature at a rate of 1℃ / min. The homogenized ingot was subjected to equal-diameter angular extrusion in a die with an angle of 90°. Before extrusion, the ingot and the die were heated to 300℃ and kept for 3h. After the insulation, the ingot was taken out and loaded into the die, and the ingot was immediately extruded along the length direction by a hydraulic press. A total of 10 passes were extruded, and the ingot length direction was reversed in each pass, and the sample was not rotated along the length direction. The extrusion rate was 4mm / min. The mold and the sample were not heated in the middle, and the surface temperature of the ingot was controlled to be 20℃ lower than the previous pass by natural cooling. The surface temperature of the ingot was 100℃ at the end of extrusion, and it was immediately quenched in water at 30℃. See attached for scanned photos of the extruded product Figure 7 The room temperature tensile mechanical properties along the length direction are listed in Table 1, and the stress-strain curves are shown in Appendix Figure 8 .
[0038] Table 1 Mechanical properties of magnesium alloy components in embodiments and comparative examples
[0039]
[0040] from Figure 2 It can be seen that after the Mg-Gd-Zn alloy was homogenized and annealed according to the process of the present invention, a dense needle-shaped LPSO phase appeared. Figure 3 , 4It can be seen that the equal-angle extrusion products in Examples 1 and 2 form a large number of kink bands. Figure 8 It can be seen that the reinforcement and plasticization effects of the Mg-Gd-Zn alloy equal-diameter angular extrusion components of Examples 1 and 2 are significantly better than those of Comparative Examples 1-3.
[0041] Combination Figure 3 and Figure 5 By comparing Example 1 with Comparative Example 1, it is found that if the homogenization annealing process of the present invention is not adopted, a large number of kink bands cannot be obtained even if the subsequent equal-channel angular extrusion process is the same, resulting in poor improvement of alloy strength and plasticity. Figure 3 and Figure 6 By comparing Example 1 and Comparative Example 2, it is found that the holding temperature of the ingot and the mold is too high, which promotes the dynamic recrystallization of the alloy and the dissolution of the LPSO phase, causing the number of kink bands to drop sharply, resulting in a significant decrease in the strength of the alloy, while the elongation is slightly improved compared to the homogenized state. Figure 4 and Figure 7 By comparing Example 2 and Comparative Example 3, it is found that the increase in the number of extrusion passes and the decrease in the final temperature lead to an increase in the degree of crushing and dissolution of the LPSO phase in the sample, grain refinement, and a decrease in the number of kink bands. Although the strength improvement effect is better, the elongation drops sharply, and the simultaneous enhancement and plasticization effect cannot be achieved. The comprehensive mechanical properties of the alloy are not as good as those of the embodiment.
[0042] The embodiments of the present invention are described above in conjunction with the accompanying drawings. In the absence of conflict, the embodiments of the present invention and the features in the embodiments can be combined with each other. The present invention is not limited to the above-mentioned specific implementations, which are merely illustrative and not restrictive. Under the enlightenment of the present invention, those skilled in the art can also make many forms without departing from the scope of protection of the present invention and the claims, all of which belong to the protection scope of the present invention.
Claims
1. A forming process of Mg-Gd-Zn alloy, characterized in that: The main steps include: A. Casting and machining a Mg-Gd-Zn alloy rectangular ingot with a cross-sectional side length of 40-60 mm and a length of 60-120 mm; the mass percentage composition of the alloy is Gd: 4.0-7.0%, Zn: 0.5-1.5%, and the rest is Mg and impurity elements that cannot be removed; B. Perform homogenization annealing treatment on the ingot; C. Perform equal-diameter angular extrusion on the homogenized annealed ingot in a die with an angle of 90°; before extrusion, heat the ingot and the die to 300-400°C and keep them warm for 1-3 hours; after the insulation, take out the ingot and put it into the die, and immediately extrude the ingot along the length direction with a hydraulic press, for a total of 4-8 passes; control the surface temperature of the ingot to be reduced by 20-50°C during each extrusion pass relative to the previous pass through natural cooling; D. Quenching treatment immediately after extrusion; In step B, the homogenization annealing process is: keep the temperature at 495-525°C for 15-40 hours, keep the temperature at 450-480°C for 3-10 hours, and then cool to room temperature at a rate of 1-10°C / min; In the step C, the surface temperature of the ingot is 140-200°C at the end of extrusion.
2. The forming process of a Mg-Gd-Zn alloy according to claim 1, characterized in that: In the step C, the extrusion rate is 4-8 mm / min.
3. The forming process of a Mg-Gd-Zn alloy according to claim 1, characterized in that: In the step C, the ingot is reversed in length direction in each equal-diameter angular extrusion pass, and the sample is not rotated in the length direction.
4. The forming process of a Mg-Gd-Zn alloy according to claim 1, characterized in that: In the step D, the water temperature for quenching treatment is 20-40°C.
5. The forming process of a Mg-Gd-Zn alloy according to claim 1, characterized in that: After quenching in step D, the room temperature yield strength of the component along the extrusion direction is ≥200MPa, the tensile strength is ≥250MPa, and the elongation after fracture is ≥10%.
Citation Information
Patent Citations
High-strength high-toughness corrosion-resistant flame-proof Mg-Gd-Y-Zn-Zr alloy and preparation method thereof
CN106756370A
High-strength Mg-Gd-Y-Zn-Zr rare-earth magnesium alloy and preparation method thereof
CN112981204A